Biometrics, distribution, and breeding notes of Savanna Nightjar (Caprimulgus affinis) in several islands of Indonesia - Wahyu Widodo; Eko Sulistyadi (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Widodo W, Sulistyadi E. 2021. Biometrics, distribution, and breeding notes of Savanna Nightjar (Caprimulgus affinis) in several islands of Indonesia. Biodiversitas 22: 2756-2762. The Savanna Nightjar Caprimulgus affinis Horsfield, 1821, a member of the family Caprimulgidae, is a sexually dimorphic, insectivorous nightjar species commonly found in Southeast Asia, including Indonesia. A least-concern species, Savanna Nightjar has diverse habitats from grasslands to shrubs to high-rise rooftops in the middle of the city. Yet, its breeding habits, particularly in urban areas, remain obscure. The purpose of the research is to discuss the biometric measurement, distribution pattern and notes of the breeding of Savanna Nightjar, through analyzing 50 specimens originating from Java, Sumatra, Billiton, Borneo, and Nusa Tenggara Islands belonging to the Museum of Zoology Bogor (MZB) in Cibinong and through a series of observation. The morphological measurements of specimens include the measurements of the length of the bodies, the wings, the tails, the bills, and the tarsi. One-way ANOVA analysis showed that the length of the body and the tail of Savanna Nightjar in Nusa Tenggara are significantly longer than those of Savanna Nightjar in Java, Sumatra, Billiton, or Borneo islands. The biometric differences could have been contributed to different habitat characteristics. Additionally, it was found the likelihood of breeding habit of Savanna Nightjar in urban areas with that of the countrysides because of the resemblance of semi-natural ecosystems in the city such as artificial rivers, small lakes, and parks to Nightjar’s open landscape natural habitats, which facilitates the breeding habits. Still, the migration of Savanna Nightjar from open country-landscapes to the metropolitan areas remains elusive and requires a more detailed study